Urban biodiversity suitability index: decoding the relationships between cities and birds - Bhakti, Tulaci; Pena, João Carlos [UNESP]; Moura, Ana Clara Mourão; Pujoni, Diego; Saliba, Lucas; Rodrigues, Marcos (Springer Nature, 2024)
The expansion of cities has increased the necessity of multidisciplinary strategies to reduce the impacts of urbanization on ecosystems. Here we present the Urban Biodiversity Suitability (UBS) Index, a spatially explicit tool that describes levels of environmental suitability for biodiversity based on several urbanistic and socioeconomic data through a wilderness mapping approach. Using a tropical metropolis as a case study (Belo Horizonte, Brazil), we applied a Multi-Criteria Analysis to produce and join four geospatial layers that we believe describe the main aspects of cities that modulate urban biodiversity distribution: human accessibility, soundscape, built artifacts and volume, and land cover. To assess the accuracy of the UBS Index, we used bird species richness, functional richness (FRic), and Rao’s Quadratic Entropy (RaoQ) based on data collected across several urban habitats (from streets to natural vegetation patches). We observed that as the suitability levels described by the UBS Index increases, higher bird species richness, FRic, and RaoQ values are also observed. Thus, quieter, less accessible urban regions, with few built artifacts, and with higher amounts of urban vegetation presented diverse bird communities. Those regions are distributed across the analyzed urban landscape, highlighting its spatial and environmental heterogeneity. The UBS Index is a simple tool that can be replicated in other cities across the globe to inform public policies for biodiversity conservation and environmental restoration in urban landscapes. Graphical abstract: [Figure not available: see fulltext.]
Keywords: Functional diversity; Multi-Criteria Analysis; Urban ecology; Urban landscape planning; Urban ornithology; Wilderness mapping